2016
DOI: 10.1186/s40249-015-0094-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the new cooperative medical scheme on financial burden of tuberculosis patients: evidence from six counties in China

Abstract: BackgroundTuberculosis (TB) patients in China encounter heavy financial burdens throughout the course of their treatment and it is unclear how China’s health insurance systems affect the alleviation of this burden under the integrated approach. This study aimed to measure reimbursement for TB services under the New Cooperative Medical Scheme (NCMS) in rural China and to evaluate changes in catastrophic health expenditure (CHE) caused by the reimbursement policies.MethodsReimbursement data were obtained from ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 39 publications
6
40
0
Order By: Relevance
“…albopictus . A similar mutation was previously described in populations from Singapore [39], China [40] and Greece [41]. In this same 1534 position other alterations were described, 1534Leu and 1534Ser in the USA [41, 42] and China [40, 41].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…albopictus . A similar mutation was previously described in populations from Singapore [39], China [40] and Greece [41]. In this same 1534 position other alterations were described, 1534Leu and 1534Ser in the USA [41, 42] and China [40, 41].…”
Section: Discussionsupporting
confidence: 65%
“…A recent survey of Ae. albopictus from several countries, in North America, Europe and Asia, reported that the 1534 Na V position is highly variable due to the presence of different mutations such as: TTC and TTT (Phe) as well as the TGC (Cys), TCC (Ser) and TTG (Leu) [40]. This means that one has to know exactly which alleles in the target population exist before applying an AS-PCR approach, like the one herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this, total costs as a proportion of pre-TB AHI and catastrophic costs were concentrated in the poorest two income quintiles. These findings are consistent with findings globally [8,37]. …”
Section: Discussionsupporting
confidence: 93%
“…India might take lessons from China where, despite social insurance schemes, the catastrophic costs due to TB have decreased marginally with no effect on inequity. One of the reasons was limited outpatient costs coverage [35,37,41]. …”
Section: Discussionmentioning
confidence: 99%